THE ROLE AND SIGNIFICANCE OF INFORMATION TECHNOLOGIES IN THE DEVELOPMENT OF MODERN SOCIETY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article provides a comprehensive analysis of the role and significance of information technologies in the development of modern society. It examines the impact of information technologies on social, economic, educational, and administrative systems, as well as their contribution to digital transformation processes. The study also addresses current challenges related to information security and highlights the importance of the rational and effective use of information technologies to ensure sustainable development.